Gadget Lab / Azarif Mizar Noor Azam - Noor Azam, Azarif Mizar (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Gadget Lab is a mobile service apps. The tag line I have proposed for this apps is "Click To Fix". Nowadays, smart phone is an important device for today's digital community ranging from children to the elderly. I proposed 'Gadget Lab app which is one stop mobile app that could help fix issues related to smart phones such as repairing phones, searching for new phones and accessories. This apps is easier for the user because everything is accessible online and at your fingertips. Users need to register and just follow the instructions and Gadget Lab will assist the user to fix the problem. Gadget Lab is a shop that has been changed and modified in terms of its name and way of selling. The original name of this company is Mizal Gadget while the founder is Mohd Mizal Aiman Bin Sulaiman. Initially, Mizal Gadget is a physical store. Mizal Gadget has been operating since 11/11/2020 until today. The word 'Gadget Lab' is a combination from gadget (selling electronics) and a lab (phone repair lab). I proposed an app for Gadget Lab to make it easier for users to use and this is easier for users to use our services which is in line with the circulation of modern times now. The art direction and concept that I used in making Gadget Lab is futuristic. The reason I used this concept is because this store sells electronics (telephones) repair services (telephones) and sells accessories for the phone and this concept fits perfectly with the design I made. For future planning, Gadget Lab will be one of the best apps on par with other well -known app names. I am very proud of the apps I proposed. Therefore, I believe this app will be one of the successful apps in Malaysia.